Attitudes and Behaviors Toward High Caffeine Intake Among Adolescents - Park, Min-Hee (Advances in Social Sciences Research Journal, 2022)
This study was conducted to identify the attitudes and behaviors of adolescents with a high caffeine intake in one region. The participants in this study were 13,484 male students and 14,408 female adolescents aged 11–18 years. Two-sample t-tests and F-tests were used for the data analysis. The results of this study showed that attitudes toward high caffeine intake among adolescents differed according to sex (t=2.923, p=0.003) and school (p<0.001). It was found that high caffeine intake was most acceptable in general high schools. In addition, 33.3% of those who had recently consumed more than once a week consumed high-caffeinated beverages. It is necessary to provide education on high-caffeine beverages, which can become addictive, along with smoking and drinking.